2004
DOI: 10.1021/la048161u
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Properties of Fullerodendron Thin Films

Abstract: Thin films of fullerodendron (C(60)(Gn-COOMe) (n = 0.5, 1.5, 2.5)), which was synthesized from fullerene and anthracenyl poly(amido amine) dendron with methyl ester terminals and different generations (G), were fabricated by the Langmuir-Blodgett (LB) and adsorption techniques. It was characterized by X-ray reflectometry that the LB films possessed well-ordered structure, although the adsorption method led to random orientation of molecules. As to C(60)(G0.5-COOMe) and C(60)(G1.5-COOMe), the LB films took a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 30 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…from slightly above room temperature up to 165 C for 18 and 180 C for 21. This behavior is quite different from that of the precursory malonate 17 which displayed two monotropic unidentified phases at 41 C and 67 C and a chiral nematic phase between 67 C and 88 C (Table 2). An increase of the mesophase stability of about 100 C as well as a near room temperature mesomorphism was thus obtained through C 60 grafting.…”
Section: Enantiotropic Smectic a Phasementioning
confidence: 63%
See 1 more Smart Citation
“…from slightly above room temperature up to 165 C for 18 and 180 C for 21. This behavior is quite different from that of the precursory malonate 17 which displayed two monotropic unidentified phases at 41 C and 67 C and a chiral nematic phase between 67 C and 88 C (Table 2). An increase of the mesophase stability of about 100 C as well as a near room temperature mesomorphism was thus obtained through C 60 grafting.…”
Section: Enantiotropic Smectic a Phasementioning
confidence: 63%
“…In the latter field, working at the air-water interface, various mono- [32][33][34][35][36][37][38] and bis- [39] [60]fullerene derivatives have been studied in the past years and showed encouraging results in terms of film quality and stability, roughness, reversibility, and transferability onto solid substrates. For example, F. Diederich and coworkers [40] or Imae and coworkers [41] showed that fullerene monoadducts bearing dendritic branches display good spreading characteristics and reversible compression/expansion behavior has been described. Working on [60]fullerene bisadducts, Nierengarten and coworkers have shown that encapsulation of the carbon sphere in a cyclic addend surrounded by either long alkyl chains [42,43] or cholesterol subunits [44] is a method of choice for obtaining stable and reversible monomolecular thin films, easily transferred onto solid substrates in order to prepare high quality LB multilayers.…”
Section: Thin Films As Induced Organization Of [60]fullerene Hexakisamentioning
confidence: 99%
“…Here, it should be noted that the formation of π-conduction channel path between the C 60 moieties is a key point for a realization of higher µ value. Especially, the FET device exhibiting a better performance may be realized with the fullerodendron films because fullerodendron molecules in the Langmuir-Blodgett (LB) films formed on SiO 2 surface are known to exhibit ordered structure [8]. This expectation is our motivation for the use of fullerodendron molecules as active layers in this study.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter field, working at the air-water interface, various [60]fullerene derivatives ranging from mono- [19][20][21][22][23][24][25], to bis- [26], up to hexa-adducts [27][28][29][30] have been studied in the past few years and showed encouraging results in terms of film quality and stability, roughness, reversibility, and transfer onto solid substrates. For example, Cardullo et al [31] or more recently Hirano et al [32] showed that fullerene mono-adducts bearing dendritic branches display good spreading characterisitics and reversible compression/ expansion behaviour has been described. Working on [60]fullerene bis-adducts, Nierengarten et al have shown that encapsulation of the carbon sphere in a cyclic addend surrounded by either long alkyl chains [33,34] or cholesterol subunits [35] is a method of choice for obtaining stable and reversible monomolecular thin films, easily transferred onto solid substrates in order to prepare high-quality LB multilayers.…”
Section: Introductionmentioning
confidence: 99%